2020
DOI: 10.1186/s12887-020-02319-y
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of acute milk consumption among asthmatic and non-asthmatic children: a randomized controlled study

Abstract: Background A commonly held public belief is that cow’s milk products increase mucus production and respiratory symptoms. Dietary milk elimination is often attempted despite lack of evidence. Our objective was to investigate whether a single exposure to cow’s milk is associated with respiratory symptoms and changes in pulmonary functions in asthmatic and non-asthmatic children. Methods We conducted a prospective double blind, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…There was high significant increase in the severity recorded (p < 0.001) in respiratory function test in allergic group (group 2) compared to control group (group 1). Koren et al (6) reported that fifty non-asthmatic children (26 assigned to the cow's milk group and 24 to the soy substitute group), and 46 asthmatic children (22 in the cow's milk group and 24 in the soy substitute group) were enrolled. Age, gender, and body mass index Zscore were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…There was high significant increase in the severity recorded (p < 0.001) in respiratory function test in allergic group (group 2) compared to control group (group 1). Koren et al (6) reported that fifty non-asthmatic children (26 assigned to the cow's milk group and 24 to the soy substitute group), and 46 asthmatic children (22 in the cow's milk group and 24 in the soy substitute group) were enrolled. Age, gender, and body mass index Zscore were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%